Case Note on BGH IX ZR 229/23 - Bork, Reinhard (European Insolvency and Restructuring Journal, 2025)
In BGH IX ZR 229/23, the German Bundesgerichtshof referred a case concerning Art. 16 EIR 2015 to the Court of Justice of the European Union for a preliminary ruling. The case involves the partial repayment of an intercompany loan between an Austrian company and its German sister company, made four months before insolvency proceedings were initiated against the German borrower. The German insolvency practitioner sought to avoid the repayment under German transaction avoidance rules. However, the loan agreement was governed by Austrian law, which no longer permitted avoidance at the time of the challenge. This case note examines how Art. 16 EIR, by purporting to protect legitimate expectations where none exist, unnecessarily complicates the application of national avoidance provisions. It further questions whether a teleological reduction of Art. 16 EIR can resolve the inconsistencies raised in this case.